Talking Book Riyadhus Sholihin in Hadith Literacy Culture for Diffables: A Case Study on Abiyoso, SLBN Citeureup and ITMI Bandung - Siti Rahmah; Zahrotun Nisa; Muhammad Yazid Arrizqi; Nurul Jamilah; Santika Choirunnisa (UIN Sunan Gunung Djati Bandung, 2021)
This study aims to discuss the effect of Riyadhus Sholihin's talking book on hadith literacy culture for the blind. This research uses qualitative methods through field studies. The results and discussion of this study include the general view of the blind, the history of the blind institution, and the influence of the Riyadhus Sholihin talking book on the culture of hadith literacy for the blind. Where Riyadus Salihin's Talking Book is an innovation designed to meet religious needs in the form of hadiths that are specifically for the visually impaired. This study concludes that the talking book has many benefits for increasing blind literacy in understanding the hadith of the Prophet. Although it is recognized that this facility has shortcomings such as the sound is not so clear, there is no repeat feature or a button to repeat certain hadith readings in one chapter, pause button, and hadith search feature However, even so, the presence of this talking book is highly expected because it can be a support and help to know and understand the Hadith of Riyadhus Sholihin. This study recommends to policy makers for the development of Riyadus Salihin's Talking Book.